Hepcidin deficiency impairs hippocampal neurogenesis and mediates brain atrophy and memory decline in mice - Xue Bai; Bing Wang; Yiduo Cui; Siqi Tian; Yi Zhang; Linhao You; Yan-Zhong Chang; Guofen Gao (Journal of Neuroinflammation, 2024)
Abstract Background Hepcidin is the master regulator of iron homeostasis. Hepcidin downregulation has been demonstrated in the brains of Alzheimer’s disease (AD) patients. However, the mechanism underlying the role of hepcidin downregulation in cognitive impairment has not been elucidated. Methods In the present study, we generated GFAP-Cre-mediated hepcidin conditional knockout mice (Hamp GFAP cKO) to explore the effect of hepcidin deficiency on hippocampal structure and neurocognition. Results We found that the Hamp GFAP cKO mice developed AD-like brain atrophy and memory deficits. In particular, the weight of the hippocampus and the number of granule neurons in the dentate gyrus were significantly reduced. Further investigation demonstrated that the morphological change in the hippocampus of Hamp GFAP cKO mice was attributed to impaired neurogenesis caused by decreased proliferation of neural stem cells. Regarding the molecular mechanism, increased iron content after depletion of hepcidin followed by an elevated level of the inflammatory factor tumor necrosis factor-α accounted for the impairment of hippocampal neurogenesis in Hamp GFAP cKO mice. These observations were further verified in GFAP promoter-driven hepcidin knockdown mice and in Nestin-Cre-mediated hepcidin conditional knockout mice. Conclusions The present findings demonstrated a critical role for hepcidin in hippocampal neurogenesis and validated the importance of iron and associated inflammatory cytokines as key modulators of neurodevelopment, providing insights into the potential pathogenesis of cognitive dysfunction and related treatments. Graphical Abstract